Diet and Physical Activity in Pertinence to Dental Caries in Children - Sirisha, P.; Shakuntala, B. S. (Research Developments in Medicine and Medical Science Vol. 2, 2023)
This chapter aims to evaluate the role of diet, physical activity, and adiposity in children from schools of two different lifestyles and its influence on dental caries. Since childhood, dental caries has been a major health concern. Caries prevalence has increased in developing countries due to a variety of factors including diet, low socioeconomic status, fluoride exposure, ethnicity, age, limited access to oral health services, and other lifestyle factors. Childhood obesity and physical activity are linked and have been shown to influence the prevalence of dental caries. A cross-sectional study was performed by recruiting 300 children in the age group of 6-10 years. A questionnaire was given to the child and parent to collect data on diet, physical activity, and adiposity.Anthropometric measurements of all the children were recorded. The findings showed that Children from Group A were known to be more obese compared to the children from Group B. A statistically significant difference was observed with the caries experience amongst the two groups. The study concluded that diet, physical activity, and adiposity all have an impact on dental caries in children. Other additional factors include parents' socioeconomic status, education, and positive dental attitude.